2016
DOI: 10.1136/jech-2015-206910
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and the use of healthcare services in Belgium

Abstract: The results partly confirm that low health literacy is associated with greater use of healthcare services, and especially of more specialised services. Improving the health literacy of the population can be an effective strategy to promote a more (cost)-effective use of the healthcare services and thus contribute to population health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
106
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 30 publications
12
106
0
6
Order By: Relevance
“…In a study involving 9617 members of a Belgian health insurance fund it was confirmed that low HL was associated with more admissions to one-day clinics, general practitioner home consultations, psychiatric consultations, ambulance transportation and with longer stays in general hospitals [31]. The study undertaken by Garcia-Codina et al [29] showed that low HL was modestly associated with low levels of physical activity, having self-perceived chronic disorders and not undertaking preventive activities.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a study involving 9617 members of a Belgian health insurance fund it was confirmed that low HL was associated with more admissions to one-day clinics, general practitioner home consultations, psychiatric consultations, ambulance transportation and with longer stays in general hospitals [31]. The study undertaken by Garcia-Codina et al [29] showed that low HL was modestly associated with low levels of physical activity, having self-perceived chronic disorders and not undertaking preventive activities.…”
Section: Discussionmentioning
confidence: 94%
“…z o.o., Rybnik, Poland) [33], a company which has considerable experience in the conduct of opinion polls. This minimum size of the sample was established after taking into consideration the size of the population (31,535,606, according to Statistics Poland, the central statistical office in Poland [34]), the fraction of 0.5, and a confidence level of 0.95. For the sample of 1000 respondents, the level of the sampling error was 3.1%.…”
Section: Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…We used the following cut off points: 0–8 is inadequate health literacy, 9–12 is limited, and 13–16 is sufficient health literacy. For more information on the HLS-EU 16 and the method of data management we used see Vandenbosch et al [19]. In this study, we divided the respondents in two groups: inadequate/limited health literacy (HL low) and sufficient health literacy (HL high).…”
Section: Methodsmentioning
confidence: 99%
“…People with limited health literacy are, on average, less knowledgeable about their disease and treatment, less able to successfully perform self-care tasks, and have poorer self-efficacy. This translates to worse health outcomes including greater hospitalization, mortality risk, use of emergency services, and decreased use of preventive care (e.g., Baker, 2006; Baker, Parker, Williams, & Clark, 1998; Berkman, Sheridan, Donahue, Halpern, & Crotty, 2011; Kindig, Panzer, Nielsen-Bohlman, 2004; Paasche-Orlow & Wolf, 2007; Vandenbosch et al, 2016). …”
mentioning
confidence: 99%